Survey of Australian maternity hospitals to inform development and implementation of a stillbirth prevention 'bundle of care'. Issue 3 (May 2020) - Andrews, C.J.; Ellwood, D.; Middleton, P.F.; Homer, C.S.E.; Reinebrant, H.E.; Donnolley, N.; Boyle, F.M.; Gordon, A.; Nicholl, M.; Morris, J.; Gardener, G.; Davies-Tuck, M.; et al.
Abstract: Background: 'Bundles of care' are being implemented to improve key practice gaps in perinatal care. As part of our development of a stillbirth prevention bundle, we consulted with Australian maternity care providers. Objective: To gain the insights of Australian maternity care providers to inform the development and implementation of a bundle of care for stillbirth prevention. Methods: A 2018 on-line survey of hospitals providing maternity services included 55 questions incorporating multiple choice, Likert items and open text. A senior clinician at each site completed the survey. The survey asked questions about practices related to fetal growth restriction, decreased fetal movements, smoking cessation, intrapartum fetal monitoring, maternal sleep position and perinatal mortality audit. The objectives were to assess which elements of care were most valued; best practice frequency; and, barriers and enablers to implementation. Results: 227 hospitals were invited with 83 (37%) responding. All proposed elements were perceived as important. Hospitals were least likely to follow best practice recommendations "all the time" for smoking cessation support (<50%), risk assessment for fetal growth restriction (<40%) and advice on sleep position (<20%). Time constraints, absence of clear guidelines and lack of continuity of carer were recognised as barriers to implementation across care practices. Conclusions: Areas for practice improvement were evident. All elements of care were valued, with increasing awareness of safe sleeping position perceived as less important. There is strong support from maternity care providers across Australia for a bundle of care to reduce stillbirth.